HUBUNGAN PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI DENGAN SIKAP TERHADAP SEKS BEBAS DI SMA NEGERI 1 SEDAYU BANTUL YOGYAKARTA - Umi Latifah; Retno Mawarti; Dwi Kartika Rukmi (MEDIA ILMU KESEHATAN, 2015)
Background : Adolescence is a period of transition from childhood to adulthood. Adolescence tend to want to learn new things so they appear to want to be double behavior, one of which is illicit sex. Based on preliminary studies conducted in SMAN 1 Sedayu obtained information some students do not understand the impact of free sex. They also lack knowledge about reproductive health. Objectives : The purpose of this studi to determine the relationship between the level of knowledge about adolescent reproductive health attitudes toward sex in SMA N 1 Sedayu Bantul Yogyakarta. Methods : The method in this research is descriptive analytic with cross sectional approach. Samples were taken with quota sampling technique in which 168 students aged 16-18 years in SMAN 1 Sedayu. The research instrument was a question naireand the results were analyzed by Kendall Tau correlation formula. Results : The level of knowledge about adolescent reproductive health in SMAN1 Sedayu Bantul mostly wellas 78 students (46.4%). Attitudes toward sex in SMA 1 Sedayu Bantul Yogyakarta Sedayu mostly positiveas many as 133 students (79.2%). The results of the correlation test of Kendall Tau obtained p- value of 0,000 <a (0,05). Conclusion : There is a significant relationship between the level of knowledge about adolescent reproductive health attitudes toward sex in SMAN 1 Sedayu Bantul, Yogyakarta. Keywords : Knowledge of Youth, Reproduction Health, Attitude Free Sex